2020
DOI: 10.1371/journal.pone.0230884
|View full text |Cite
|
Sign up to set email alerts
|

Global expression and CpG methylation analysis of primary endothelial cells before and after TNFa stimulation reveals gene modules enriched in inflammatory and infectious diseases and associated DMRs

Abstract: Endothelial cells are a primary site of leukocyte recruitment during inflammation. An increase in tumor necrosis factor-alpha (TNFa) levels as a result of infection or some autoimmune diseases can trigger this process. Several autoimmune diseases are now treated with TNFa inhibitors. However, genomic alterations that occur as a result of TNF-mediated inflammation are not well understood. To investigate molecular targets and networks resulting from increased TNFa, we measured DNA methylation and gene expression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 40 publications
0
15
0
Order By: Relevance
“…For each out of 8 test samples, we constructed a subnetwork selecting 140 the most relevant genes and deleting singletones, that lead to subnetworks consisting of mainly 130 vertices. Remarkably, the green gene module, which was the most strongly correlated one with TNFα upregulation (Rhead et al, 2020) showed significant association (adjusted p-value < 0.05) with the combined set of subnetwork genes, with genes found in the majority of subnetworks and also with 5 of the 8 subnetworks (Supplementary File S1). At the same significance level the turquoise gene module described in (Rhead et al, 2020) was strongly associated with 2 of 8 subnetworks and with genes found in all 8 subnetworks.…”
Section: Genes Selected By Glrp Correlate With Modules Identified By mentioning
confidence: 99%
See 4 more Smart Citations
“…For each out of 8 test samples, we constructed a subnetwork selecting 140 the most relevant genes and deleting singletones, that lead to subnetworks consisting of mainly 130 vertices. Remarkably, the green gene module, which was the most strongly correlated one with TNFα upregulation (Rhead et al, 2020) showed significant association (adjusted p-value < 0.05) with the combined set of subnetwork genes, with genes found in the majority of subnetworks and also with 5 of the 8 subnetworks (Supplementary File S1). At the same significance level the turquoise gene module described in (Rhead et al, 2020) was strongly associated with 2 of 8 subnetworks and with genes found in all 8 subnetworks.…”
Section: Genes Selected By Glrp Correlate With Modules Identified By mentioning
confidence: 99%
“…Remarkably, the green gene module, which was the most strongly correlated one with TNFα upregulation (Rhead et al, 2020) showed significant association (adjusted p-value < 0.05) with the combined set of subnetwork genes, with genes found in the majority of subnetworks and also with 5 of the 8 subnetworks (Supplementary File S1). At the same significance level the turquoise gene module described in (Rhead et al, 2020) was strongly associated with 2 of 8 subnetworks and with genes found in all 8 subnetworks. In addition, both the green and the turquoise modules showed moderate association (adjusted p-value < 0.1) with the majority of gene sets defined on the basis of the test subnetworks.…”
Section: Genes Selected By Glrp Correlate With Modules Identified By mentioning
confidence: 99%
See 3 more Smart Citations